2014
DOI: 10.1108/mip-08-2013-0127
|View full text |Cite
|
Sign up to set email alerts
|

Marketing culture and business performance

Abstract: 2014),"The impact of cultural sensitivity and information exchange on relationship quality", Marketing Intelligence & Planning, Vol. 32 Iss 7 pp. 754-768 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, three studies (9.09%) measured business performance by concentrating only on financial performance . For instance, Al-Mohammad et al (2014) measured financial performance by using items such as sales volume and profitability. Secondary data analysis was also used for measuring financial performance (e.g.…”
Section: Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, three studies (9.09%) measured business performance by concentrating only on financial performance . For instance, Al-Mohammad et al (2014) measured financial performance by using items such as sales volume and profitability. Secondary data analysis was also used for measuring financial performance (e.g.…”
Section: Review Findingsmentioning
confidence: 99%
“…A number of articles focused on organizational/operational factors and their influence on restaurants’ business performance. For example, it was found that business performance is positively influenced by internal marketing and market orientation (Brown et al, 2014; Salehzadeh et al, 2017), marketing culture (Al-Mohammad et al, 2014), innovation activities (Lee et al, 2016a; 2016b), product innovation (Cho et al, 2018), organizational culture (Jogaratnam, 2017a), asset growth (Mun and Jang 2020), inventory turnover (Park and Kim 2020), and franchising (Madanoglu et al, 2011).…”
Section: Review Findingsmentioning
confidence: 99%